PERLINDUNGAN TERHADAP PEKERJA WANITA YANG SEDANG HAMIL - Permatawati, Rezki; Purwanti, Ni Putu (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014, 2014)
Some companies that require women to voluntarily resign when she was pregnantbecause pregnant women are considered not able to carry out works to the maximum so thatit will interfere with the productivity of the company. Purposed of the examination is toknowed the rights of pregnant women workers. This type of research is a kind of normativelegal research with the approach of legislation and approach to the concept, and usingdescriptive analysis, analysis and argumentation. Protection of women workers who arepregnant stipulated in the Decision Manpower and Transmigration Minister of the RepublicIndonesia Number: Kep-224/Men/2003 About Liability Employers Who Employs The LaborOf Women Workers Between 23.00 to 07.00, the Minister of Labor Regulations of TheRepublic Indonesia Number: Per-03/MEN/1989 On The Prohibition Termination OfEmployment For Woman Workers Because Of Married, Pregnancy and Childbirth, LawNumber 13 year 2003 On Employment.
Keywords: Protecting, Worker, Woman, Pregnant